2014
DOI: 10.1080/21606544.2014.972467
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal product differentiation and policy adjustment in the presence of abatement subsidies and emission taxes

Abstract: There are important examples of countries which have implemented policies to promote pollution abatement activities in sectors characterised by some degree of product differentiation. This paper examines the role of product differentiation on optimal policy and industry emissions in a Cournot oligopoly model in the presence of abatement technology, abatement subsidies and emission taxes. The analysis indicates that as products become more differentiated the government can afford a tax increase due to the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Ashraf et al (2013) find that offering product information to the consumers can greatly enhance the effect of subsidy program in increasing the adoption of health product in developing countries. Taking the perspective of the producer firm, Bansal and Gangopadhyay (2003) and Gautier (2015) analyze how tax-subsidy policies impact competing firms' output decisions. There are other related studies that analyze the interaction between the consumers and the private donors (e.g., Ben-Zion and Spiegel 1983).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ashraf et al (2013) find that offering product information to the consumers can greatly enhance the effect of subsidy program in increasing the adoption of health product in developing countries. Taking the perspective of the producer firm, Bansal and Gangopadhyay (2003) and Gautier (2015) analyze how tax-subsidy policies impact competing firms' output decisions. There are other related studies that analyze the interaction between the consumers and the private donors (e.g., Ben-Zion and Spiegel 1983).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Youssef and Dinar (2011) analysed the optimal combination of emission taxes and R&D subsidies in polluting industries, while David and Sinclair‐Desgagné (2010) examined pollution abatement subsidies and emission taxes in the eco‐industry. Gautier (2015) considered product differentiation and policy adjustment in the presence of abatement subsidies and emission taxes. Furthermore, Lee and Tomaru (2017) examined different policy combinations but demonstrated that R&D investment combined with an output subsidy can be taxed.…”
Section: Introductionmentioning
confidence: 99%
“…Gautier L discussed the impact of product differentiation on optimal decisions in the Cournot model. Studies have shown that when subsidies and emission reduction technologies exist, increased product differentiation can enable governments to withstand tax increases [23]. Kuo T C et al use a supply chain network design to analyze the trade-off between carbon emission and cost.…”
Section: Introductionmentioning
confidence: 99%